2020
DOI: 10.1111/exd.14113
|View full text |Cite
|
Sign up to set email alerts
|

IL‐15 and IL‐23 synergize to trigger Th17 response by CLA+ T cells in psoriasis

Abstract: IL‐15 has emerged as a potentially relevant target in the IL‐17 response in psoriasis. However, its mechanism is poorly characterized in humans. IL‐15 and IL‐23 are constitutively expressed in the psoriatic lesion. Also, IL‐15 is considered a susceptibility‐associated gene in psoriasis, as are IL‐23R, and HLACW6. Here, we studied the effect of IL‐15 and IL‐23 stimulation on the cytokine response of CLA+/CLA‐ T cells from 9 psoriasis patients and 3 healthy control subjects. To this end, CLA + and CLA‐ T cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…IL-15 and IL-23, both present in psoriatic lesions, have been shown to synergize with CLA + T cells and autologous epidermal cells to produce IL-17A and IL-17F in PSO. This phenomenon occurs without the use of any exogenous stimulus, in a major histocompatibility complex (MHC)-dependent way, and independently of resident T cells (18), but it does not take place using CLA − T cells or cells from healthy controls. This is an example of how psoriatic skin cytokine microenvironment interacts specifically with skin-related memory T cells generating the IL-17 response critical for PSO initiation and maintenance.…”
Section: Psoriasismentioning
confidence: 99%
“…IL-15 and IL-23, both present in psoriatic lesions, have been shown to synergize with CLA + T cells and autologous epidermal cells to produce IL-17A and IL-17F in PSO. This phenomenon occurs without the use of any exogenous stimulus, in a major histocompatibility complex (MHC)-dependent way, and independently of resident T cells (18), but it does not take place using CLA − T cells or cells from healthy controls. This is an example of how psoriatic skin cytokine microenvironment interacts specifically with skin-related memory T cells generating the IL-17 response critical for PSO initiation and maintenance.…”
Section: Psoriasismentioning
confidence: 99%
“…This is not surprising, considering that humans and rodents are separated by an estimated 96 million years of evolution 21 . Addressing this fact, many studies are being conducted on patient‐derived primary skin cells, including human keratinocytes, 22‐25 melanocytes, 26‐30 fibroblasts 31‐34 and cell co‐cultures 35‐37 . However, typical in vitro culture conditions fail to replicate and, in fact, do not come close to imitating the biomechanical and biochemical complexity of the microenvironment in which cells exist and to which they respond to in native tissues.…”
Section: Bridging the Gap Between “Simplicity” Of In Vitro And Complementioning
confidence: 99%
“…Also, the co‐culture of dermal fibroblasts and keratinocytes can model particulate matter exposure, where factors released by keratinocytes after heavy metal and hydrocarbon exposure can mediate dermal collagen degradation 36 . In other examples, co‐cultures of vitiligo patient‐derived CD4 + and CD8 + T cells, 52 or keratinocytes and T cells from psoriasis patients, 37 can be used to advance our understanding of skin disease immunopathogenesis.…”
Section: What Organotypic Cultures Can and Can't Domentioning
confidence: 99%
“…IL17 is one of the key effector molecules that promote a hyperproliferative response in keratinocytes, leading to uncontrolled epidermal expansion and psoriatic plaque formation 4,13,19,20 . IL15 has also emerged as a potential target in PSO 21 . Association between IL‐15 single nucleotide polymorphisms (SNPs) and PSO has been reported, 22 and an ex vivo co‐culture study found that IL15 synergizes with IL23 to activate cutaneous lymphocyte‐associated antigen (CLA)+ T cells to produce high levels of IL17A/F 21 .…”
Section: Immunopathogenesismentioning
confidence: 99%
“…IL15 has also emerged as a potential target in PSO 21 . Association between IL‐15 single nucleotide polymorphisms (SNPs) and PSO has been reported, 22 and an ex vivo co‐culture study found that IL15 synergizes with IL23 to activate cutaneous lymphocyte‐associated antigen (CLA)+ T cells to produce high levels of IL17A/F 21 . Compared to PSO, generalized pustular psoriasis expresses higher levels of IL1 and IL36 in the skin, 23 in addition to IL17 and IL23, leading to excessive and persistent skin inflammation that can manifest systemically 23 …”
Section: Immunopathogenesismentioning
confidence: 99%